The use of macrozoobenthos community to determinethe Senapelan River water quality - Fajri, Nur El; ', Meinita; ', Adriman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Senapelan River is one of the polluted river in Pekanbaru. This research aims to determine the water quality of the river based on physical, chemical and biological parameters, namely the macrozoobenthos community. This research was conducted from May to June 2015. There were three stations, 3 sampling points/ station. Water samples were taken 3 times, once per week. Water quality parameters measured were temperature, turbidity, brightness, current speed, total suspended solid, depths, pH, DO, BOD5, and types of makrozoobentos present.Macrozoobenthos found during the research consist of 5 species that were belonged to three classes, namely Gastropoda (Ampullacea pila, Radix ovata and Viviparus sp) , Oligochaeta (Tubifex sp) ,and Clitellata (Hirudo medicinalis). Water quality parameters in the Senapelan River were as follows: temperature 27-28 0C, turbidity 20.7 to 50 NTU, transparency 8-17 cm, current speed 3.19 to 7.36 cm/sec, TSS 5.67 to 15 mg/L, depth 17-138 cm, pH 6-7, DO 1.68 to 4.79 mg/L, and BOD5 ranged from 10.59 to 17.07 mg/Ll.The value ofBelgium BioticIndex metode of the Senapelan River was 2-3, indicates that this river is badly polluted.Keyword: Senapelan River, water quality, Belgium Biotic Index, Macrozoobenthos